Droga . pismo Konfederacji Polski Niepodległej, no. 22, 1986 - Konfederacja Polski Niepodległej, ed. committee (Wydawnictwo Polskie, 1986)
Creation and circulation: Issues no. 12-13 from 1981 prepared for print but not published due to the introduction of the Martial Law, when publication ceased to be publised. Republished underground in 1984